1991
DOI: 10.1021/jm00112a036
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of stilbene and dihydrostilbene derivatives as potential anticancer agents that inhibit tubulin polymerization

Abstract: J. Med. Chem. dimethylformamide (1 mL) was treated with 60% sodium hydride in oil (20 mg) for 20 min, and then with ethyl iodide (0.02 mL) for 20 min longer. The mixture was concentrated to dryness at 0.1 mm, taken up in ethyl acetate, washed with sodium bicarbonate solution, dried (Mg#O$, concentrated to dryness, and triturated with ether to afford the ester as an off-white solid, mp 110-118 OC (30 mg, 31%). Similarly, 3s was prepared from 3a i991,34, m 9 -2 5~ 2579 through the use of tert-butyl 4-(2-aminoeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
219
2
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(246 citation statements)
references
References 9 publications
15
219
2
5
Order By: Relevance
“…Strong orthoeffects from substituents on phosphorus were already well known through the work of McEwen and co-workers 75, 76 and these had been extended to the Wittig reaction, although with conflicting results. 77,78 It was also known that Z-selectivity in stilbene synthesis could be induced by ortho-substituents with heteroatom lone pairs on the aldehyde 79,80 However, remarkably, we found that this latter Z-selectivity could be substantially augmented by an additional ortho-substituent on the benzylide, despite the fact that such a substituent would ordinarily lead to E-selectivity. This counter-intuitive cooperative effect was strong enough to be preparatively useful (Z/E up to 95:5) and the resulting Z-2,2'-disubstituted stilbenes have been used to good effect in synthesis by others.…”
Section: Our Interest In This Areamentioning
confidence: 56%
“…Strong orthoeffects from substituents on phosphorus were already well known through the work of McEwen and co-workers 75, 76 and these had been extended to the Wittig reaction, although with conflicting results. 77,78 It was also known that Z-selectivity in stilbene synthesis could be induced by ortho-substituents with heteroatom lone pairs on the aldehyde 79,80 However, remarkably, we found that this latter Z-selectivity could be substantially augmented by an additional ortho-substituent on the benzylide, despite the fact that such a substituent would ordinarily lead to E-selectivity. This counter-intuitive cooperative effect was strong enough to be preparatively useful (Z/E up to 95:5) and the resulting Z-2,2'-disubstituted stilbenes have been used to good effect in synthesis by others.…”
Section: Our Interest In This Areamentioning
confidence: 56%
“…We therefore could expect activity at the colchicine binding site of tubulin for suitably substituted benzoxepins. This type of benzoxepin structure will also avoid the inactivation observed for the conventional combretastatin derivatives, which is caused by cis-trans isomerism of the olefinic bond observed in vivo 23 . We have investigated the development of the benzoxepin type scaffold as a conformationally restricted analog for combretastatin, where the seven-membered oxygen containing ring forms a slightly flexible bridge on the ethylene bond linking the combretastatin rings A and B. Fifteen compounds have been synthesized and evaluated for specific antiproliferative activity in two human breast cancer cell lines, MCF-7 (estrogen receptor positive) and MDA-MB 231(estrogen receptor negative).…”
Section: Introductionmentioning
confidence: 99%
“…This compound was found to inhibit tubulin polymerization, and competitively inhibit the binding of radiolabeled colchicines to tubulin. Investigation of combretastatins revealed that combrestastatin A-4 was active against multidrug resistant (MDR) cancer cell lines (McGown, et al, 1990;Lin, et al, 1988 andCushman, et al 1991). Combretastatin (A-4), as well as its trans-isomer and a number of related substances, has been found to cause mitotic arrest in cells in culture at cytotoxic concentrations.…”
Section: Introductionmentioning
confidence: 99%